Fresh fruit and vegetables: a world of multiple interactions : the case of the Buenos Aires Central Wholesale Market (BACWM) - Viteri, Maria Laura (Wageningen University, 2020)
Tesis para obtener el grado de Doctor of Philosophy (PhD), de la Wageningen University, en diciembre de 2010